2009
DOI: 10.1021/jo900059y
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyldiselenide-Catalyzed Selective Oxidation of Activated Alcohols with tert-Butyl Hydroperoxide: New Mechanistic Insights

Abstract: Diselenides are known precatalysts for catalytic oxidations. The use of these widely available compounds as catalysts for the oxidation of alcohols was investigated, still leaving many mechanistic questions to be answered. By using a range of analytical techniques, we found evidence for the unexpected involvement of seleninic anhydride in the catalytic mechanism. The activation time of the diselenide and its influence on the oxidation reaction itself was also investigated. On the basis of these findings, an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…We know that, at this stage, the BSA is not yet formed since we have observed that the oxidation of benzyl alcohol does not start when added after 10 min. [8] In contrast, if we added the benzyl alcohol after 40 min, an equimolar amount was oxidized (95 % yield). To further investigate the nature of the active species, we turned to in situ Raman and IR spectroscopy.…”
Section: Spectroscopic Studies Of the Formation Of Bsa As The Active mentioning
confidence: 99%
See 2 more Smart Citations
“…We know that, at this stage, the BSA is not yet formed since we have observed that the oxidation of benzyl alcohol does not start when added after 10 min. [8] In contrast, if we added the benzyl alcohol after 40 min, an equimolar amount was oxidized (95 % yield). To further investigate the nature of the active species, we turned to in situ Raman and IR spectroscopy.…”
Section: Spectroscopic Studies Of the Formation Of Bsa As The Active mentioning
confidence: 99%
“…[17] Oxidation of an Aliphatic Alcohol: 1-Decanol Previously we had shown that, using an oxidant and substrate feed in a loop cycle, high selectivity and efficiency can be attained with diphenyl diselenide as the oxidation catalyst. [8] To further explore the scope of our substituted diselenides, a catalytic test was performed with 5 mol-% diselenide and 1-decanol as the substrate. Unfortunately, the maximum yield of decanal attained was 8 %, which declined over time as it was further oxidized to capric acid.…”
Section: Substituted Diaryl Diselenides In the Catalytic Oxidation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, the oxidation of benzyl alcohol 8 was achieved by replacing terminal oxidant N-chloro-4-chlorobenzenesulfonamide sodium salt 2 with tert-butyl hydroperoxide (TBHP) using diphenyl diselenide 9 as catalyst (Scheme 2). 26 The oxidation was investigated in different polar and non-polar solvents and benzaldehyde 10 was obtained in highest yields using toluene as solvent (Scheme 2). Additionally, the over oxidized product benzoic acid 11 was also observed but only as a minor product.…”
Section: Selenium-catalysed Oxidation Of Alcoholsmentioning
confidence: 99%
“…本文将报道我们所取得的阶段性研究进展. 基于文献报道 [7,8,12] 和上述实验结果, 我们提出了可 能的反应机理(Scheme 1). 在过氧化氢的氧化下, 二硒 醚可被转化为高价硒活性催化物种 [7,8] .…”
Section: 苯酚选择性氧化制备对苯醌是一个有重要工业应unclassified